Representasi Nilai Filosofis dan Sosiologis dalam Lelagon Lumbung Desa: Kajian Semiotika Roland Barthes - Teki Teguh Setiawan; Pitutur Tustho Gumawang; Wisnu Samodro (Lembaga Pengembangan Kinerja Dosen, 2026)
Traditional artworks, amidst the tide of modernization and digitalization, face the challenge of being stigmatized as static relics of the past. However, in the midst of increasingly modern civilization, traditional artworks are perceived to possess philosophical values ​​for the younger generation. The meanings contained in traditional songs possess a social perspective lacking in most traditional songs composed in the modern era. The purpose of this article is to examine the lyrics of Ki Nartosabdo's song